Effects of hyperbaric oxygen therapy after spinal cord injury: systematic review - Falavigna,Asdrubal (2009)
OBJECTIVE: to conduct a systematic review of experimental and clinical studies evaluating the effect of hyperbaric oxygen therapy on the spinal cord injury. METHODS: ninety-three studies were identified in the database Pubmed. Among these, through a set of inclusion/exclusion criteria, 11 articles published between 1963 and 2009 were selected. In the nine experimental studies, different ways to apply the treatment were observed. The measured outcomes were: functional, histological, biochemical and electrophysiological. RESULTS: in most of the studies, the results show recovery of locomotor function, histology and/or biochemical features. Regarding the two studies in clinical samples, the results are controversial. The samples are heterogeneous and the application of hyperbaric oxygen therapy is not the same for all patients in each study. CONCLUSION: considering the results of this review, further studies are necessary to define the role of hyperbaric oxygen therapy in acute spinal cord injury.